Intelligent bank management simulation system for Malaysian financial institutions (IBMS) / Mahadevan Supramaniam - Mahadevan , Supramaniam (2003)
This research is about proposing an idea of simulation based training system, which could provide comprehensive information about the operations and management of banks. A prototype for the simulation based training system for local banks is developed based on the idea. The prototype was used to evaluate the participation of bank executives in using a simulation based training system with the techniques and methods of financial analysis of the banking firm. It provides them an opportunity to apply the methods in a realistic environment. The prototype, namely Intelligent Bank Management Simulation System is a web based simulation training system, which was developed in accordance to Malaysian Banking system. The prototype was modeled as a client server system. It was developed through Active Server Pages (ASP) server scripting environment and MySQL Server was used to set up the web database for the system. Intelligent Bank Management Simulation Training system involves the participation of an instructor and a group of participants to initiate a training session. The details of the training are elaborated in detail in the project report. The report also includes the results of evaluation done on the system by the local bankers to initiate the idea of using a simulation based training system in Malaysian Financial Institutions.